2021
DOI: 10.3389/fphar.2021.615202
|View full text |Cite
|
Sign up to set email alerts
|

BNSTAVGABA-PVNCRF Circuit Regulates Visceral Hypersensitivity Induced by Maternal Separation in Vgat-Cre Mice

Abstract: Visceral hypersensitivity as a common clinical manifestation of irritable bowel syndrome (IBS) may contribute to the development of chronic visceral pain. Our prior studies authenticated that the activation of the corticotropin-releasing factor (CRF) neurons in paraventricular nucleus (PVN) contributed to visceral hypersensitivity in mice, but puzzles still remain with respect to the underlying hyperactivation of corticotropin-releasing factor neurons. Herein, we employed maternal separation (MS) to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…However, the impact of different environments qualities on adolescent behavior and their mechanisms remains poorly underexplored. There is growing evidence that early life stress may permanently damage the developing brain, adversely affect behavior in adulthood, and increase the risk of chronic pain and psychopathology (17)(18)(19)(20)(21)(22)(23). However, little is known about the effects on puberty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the impact of different environments qualities on adolescent behavior and their mechanisms remains poorly underexplored. There is growing evidence that early life stress may permanently damage the developing brain, adversely affect behavior in adulthood, and increase the risk of chronic pain and psychopathology (17)(18)(19)(20)(21)(22)(23). However, little is known about the effects on puberty.…”
Section: Discussionmentioning
confidence: 99%
“…Early life stress was closely associated with the development of chronic pain and psychiatric disorders (17)(18)(19)(20)(21)(22)(23). Besides, early life stress can affect neuroinflammation, and neuroinflammation plays a role in chronic pain and psychiatric pathology (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism of MS-induced visceral hypersensitivity has been widely studied in adult rats and mice (Tang et al, 2017;Fan et al, 2020;Chen et al, 2021;Huang et al, 2021). It was reported that sensitization of corticotropin-releasing factor (CRF) neurons in the hypothalamic paraventricular nucleus (PVN) plays an important role in the pathogenesis of visceral pain (Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal distention (CRD) is a widely used method for assessing visceral hypersensitivity (Larsson et al, 2003;Christianson and Gebhart, 2007;Annahazi et al, 2009;Huang et al, 2021). However, CRD for evaluation of visceral sensitivity has not been reported in post-weaning mice.…”
Section: Introductionmentioning
confidence: 99%
“…), and stimulate adrenocorticotropic hormone secretion from the pituitary ( Kalantaridou et al, 2010 ). CRF could mediate general responses to stress and other responses such as visceral hyperalgesia ( Elman and Borsook, 2016 ; Chess-Williams et al, 2021 ; Huang et al, 2021 ). Other stress response-relevant brain regions include the prefrontal cortex, amygdala, and hippocampus ( Kalantaridou et al, 2010 ).…”
Section: Implications For Integrated Mechanismsmentioning
confidence: 99%